2016
DOI: 10.1128/aac.02815-15
|View full text |Cite
|
Sign up to set email alerts
|

Secreted Compounds of the Probiotic Bacillus clausii Strain O/C Inhibit the Cytotoxic Effects Induced by Clostridium difficile and Bacillus cereus Toxins

Abstract: Although the use of probiotics based on Bacillus strains to fight off intestinal pathogens and antibiotic-associated diarrhea is widespread, the mechanisms involved in producing their beneficial effects remain unclear. Here, we studied the ability of compounds secreted by the probiotic Bacillus clausii strain O/C to counteract the cytotoxic effects induced by toxins of two pathogens, Clostridium difficile and Bacillus cereus, by evaluating eukaryotic cell viability and expression of selected genes. Coincubatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 52 publications
1
57
0
1
Order By: Relevance
“…We are currently investigating if the effect of MYb115 is mediated by an indirect mechanism-i.e., through reinforcement of intestinal barriers, increased damage repair, or activation of other defense responses. However, we cannot exclude that MYb115 has a direct effect on the Cry toxins released by the BT spores-e.g., by degradation of the toxins-as was previously shown for a protease secreted by the probiotic B. clausii that inhibits the toxic effects of B. cereus toxins in a cytotoxicity assay using mammalian cell lines [20].…”
Section: Resultsmentioning
confidence: 64%
“…We are currently investigating if the effect of MYb115 is mediated by an indirect mechanism-i.e., through reinforcement of intestinal barriers, increased damage repair, or activation of other defense responses. However, we cannot exclude that MYb115 has a direct effect on the Cry toxins released by the BT spores-e.g., by degradation of the toxins-as was previously shown for a protease secreted by the probiotic B. clausii that inhibits the toxic effects of B. cereus toxins in a cytotoxicity assay using mammalian cell lines [20].…”
Section: Resultsmentioning
confidence: 64%
“…The antagonistic activity of aninocoumacin A was also documented against enteric E. faecium and Shigella flexneri. An interesting communication by Ripert et al (2016) revealed that the probiotic B. clausii O/C strain protected vero and Caco-2 cells from the cytotoxic effect of Clostridium difficili and B. cereus toxins. This activity was mediated by serine protease(s) of B. clausii .…”
Section: Bacillus : Probiotic Attributes In Gutmentioning
confidence: 99%
“…offers higher acid tolerance and better stability during heat processing and low temperature storage ( Bader et al, 2012 ). Additionally, they have also been shown to possess pathogen exclusion, anti-oxidant, antimicrobial, immuno-modulatory ( Lefevre et al, 2015 ; Shobharani et al, 2015 ; Ripert et al, 2016 ) and food fermentation ( Terlabie et al, 2006 ) abilities.…”
Section: Introductionmentioning
confidence: 99%
“…The intrinsic antibiotic resistance in probiotics is considered advantageous in cases of antibiotics-probiotics combination prescriptions to restore healthy gut [14,15]. The mode of action of B. clausii as a probiotic is not clear, but the strains have been reported to secrete some proteins that are involved in the immunomodulatory mechanism, adaptation and their colonization in the human gastrointestinal tract (GIT) [12,13,[16][17][18]. Uniquely, B. clausii harbor erm (34) gene that imparts the resistance to erythromycin.…”
Section: Introductionmentioning
confidence: 99%
“…Various clinical trials and molecular studies [8,13,16,[20][21][22][23] have been performed to identify the major features that demarcate B. clausii probiotic strains from other Bacillus spp., but still, the genomic reasons of its probiotic activity have not been reported before. Therefore, we sequenced the composite genome sequence of Bacillus clausii (composite of all four strains of B. clausii used in the probiotic formulation) from Enterogermina®, an oral probiotic, marketed by Sanofi in India.…”
Section: Introductionmentioning
confidence: 99%